Micromechanisms associated with the dynamic compressive failure of hot-pressed boron carbide. (September 2015) - Farbaniec, L.; Hogan, J.D.; Ramesh, K.T.
Graphical abstract: Wing crack observed in the boron carbide microstructure compared with the wing crack model. Abstract : Brittle failure in boron carbide has been studied in dynamic uniaxial compression using a Kolsky bar technique. A detailed study of fragments was performed using SEM-EDS, to identify the mechanisms responsible for failure. Microstructural characterization and fracture surface observations revealed that carbon inclusions oriented at certain angles with respect to the direction of loading might act as possible crack initiation sites. Cracks developed from these inhomogeneities had a tensile character, and were linked to the wing crack mechanism.